2019
DOI: 10.1111/papr.12860
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐procedural Management of Implanted Spinal Cord Stimulators in Patients Undergoing Radiofrequency Ablation: A Case Report and Manufacturer‐Specific Recommendations

Abstract: Introduction Radiofrequency ablation (RFA) and spinal cord stimulation (SCS) are 2 common modalities used in management of various pain conditions. RFA generates heat and an electromagnetic field that can theoretically interfere with the functionality and longevity of the SCS device. This is problematic for patients who need RFA and have previously undergone implantation of an SCS device. Case Description We present a case highlighting the safe use of bipolar RFA in a patient who had previously undergone impla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Increased risk of damage or injury may occur if the RFA needle is near enough to the IPG, SCS lead, or any tissue near the leads. 17 In contrast, it has been reported that use of a bipolar RFA needle, which uses one active electrode and one ground electrode with a shorter inter-distance, has decreased risk since it provides the opportunity for precise and predictive ablation of the target. 19 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased risk of damage or injury may occur if the RFA needle is near enough to the IPG, SCS lead, or any tissue near the leads. 17 In contrast, it has been reported that use of a bipolar RFA needle, which uses one active electrode and one ground electrode with a shorter inter-distance, has decreased risk since it provides the opportunity for precise and predictive ablation of the target. 19 …”
Section: Resultsmentioning
confidence: 99%
“…SCS devices are typically utilized in the setting of chronic axial or appendicular neuropathic pain, radicular pain, complex regional pain syndrome (CRPS), and failed back surgery syndrome, all of which are approved indications by the Food and Drug Administration (FDA). 17 Additional indications exist including chronic intractable angina, peripheral vascular disease, postherpetic neuralgia, central pain from multiple sclerosis (MS), visceral pain, and painful spasms of atypical stiff limb syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…However, the literature also includes two reported cases of RF-induced spinal cord stimulator malfunction and one case of DBS malfunction. Interestingly, both the case by Jeon et al in 2010 and the subsequent case by Abdullah et al in 2020 describe what appears to be spontaneous activation of a cervical spinal cord stimulator device during RF treatment of the cervical medial branches (despite both systems being turned off prior to RF), which resulted in painful upper extremity paresthesias 88 90. Fortunately, the painful paresthesia in both cases ceased after stopping the RF treatment, and there was no reported long-term harm to either patient or device in both instances.…”
Section: Special Circumstancesmentioning
confidence: 99%
“…RF procedures are often used as adjunctive pain treatments in patients with various implanted neuromodulation devices 88. The concomitant use of RF and implanted neuromodulation devices has been historically considered safe, especially when these devices are turned off prior to RF treatment.…”
Section: Special Circumstancesmentioning
confidence: 99%
See 1 more Smart Citation